Chemical Constituents of Pellionia latifolia (Blume) Boerl. (Urticaceae) Collected in Yen Bai - Thi Tuyet Anh, Dang; Thi Hien, Nguyen; Thi Phuong, Hoang; Tuan Anh, Nguyen; Quoc Anh, Ngo; Hong Anh, Duong; Hung Viet, Pham; Van Tuyen, Nguyen (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 4, 2018)
Abstract: Pellionia latifolia  (Blume) Boerl . (Urticaceae) , found in a number of localities in Northwest Vietnam, such as Son La, Lao Cai, Yen Bai, Ha Giang provinces, is used in Vietnamese traditional medicine for treatment of several liver-related diseases. Phytochemical investigation of the ethanol extract of Pellionia latifolia  led to the isolation of five compounds: ( 1 ) cycloartenol, ( 2 ) b-sitosterol, ( 3 ) oleic acid, ( 4 ) glucose and ( 5 ) b-sitosterolglucoside. These compounds’ chemical structures were defined by spectroscopic methods including MS, 1 H-NMR and 13 C-NMR, and comparison of the current spectral data with the previously reported values. Keywords: Pellionia latifolia , chemical composition, cycloartenol. References [1] Lin Qi; Ib Friis, C. Melanie Wilmot-Dear, Pellionia, Flora of China 5 ( 2003) 122-127. [2] Võ Văn Chi, Từ điển cây thuốc Việt Nam, Nhà xuất bản Y học, 2018. [3] Alain Milon, Yoichi Nakatani, Jean-Pierre Kintzinger, Guy Ourisson, The Conformation of Cycloartenol Investigated by NMR and Molecular Mechanics, Helvetica Chimica Acta 72 (1989) 1-11. [4] Nguyễn Thị Bích Thu, Nguyễn Thị Quỳ, Do Young Yoon, Phạm Kim Mãn, Đoàn Thị Nhu, Bước đầu nghiên cứu tác dụng ức chế của cà gai leo đối với gen gây ung thư của virus, Tạp chí Dược Liệu 4 (6) (2001) 118-121. [5] Firouz Matloubi Moghaddam, Mahdi Moridi Farimani, Sabah Salahvarzi, and Gholamreza Amin, Chemical Constituents of Dichloromethane Extract of Cultivated Satureja khuzistanica, Evid Based Complement Alternat Med. 4(1) (2007) 95-98. [6] Kimihiro Yoshimoto, Yoshitaka Itatani, Yoshisuke Tsuda. 13C-Nuclear Magnetic Resonance (NMR) spectra of O-Acylglucoses. Additivity of Shift Parameters and Its Application to Structure Elucidations. Chem.Pharm.Bull. 28 (7) (1980) 2065-2076. [7] Nguyễn Minh Khai, Phạm Kim Mãn, Nguyễn Bích Thu, Vũ Kim Thu, Phạm Thanh Trúc, Lã Kim Oanh, Nguyễn Văn Mùi, Trịnh Thị Xuân Hòa. Nghiên cứu điều chế thuốc Haina điều trị viêm gan B mạn hoạt động từ Cà gai leo (Solanum hainanense), Tạp chí Dược Liệu 4(2) (2001) 68-71. [8] Zhanwu Sheng, Haofu Dai, Siyi Pan, Hui Wang, Yingying Hu and Weihong Ma, Isolation and Characterization of an α-glucosidase inhibitor from Musa spp. (Baxijiao) flowers, Molecules 19 (2014) 10563-10573.